Schizophrenia treatment with a combination of two LAI antipsychotics: A case report - Jarosz, Marcin; Badura-Brzoza, Karina (Frontiers in Psychiatry, 2022)
Preventing the relapse of a psychotic episode is a challenge for the treatment of schizophrenia. Patients with schizophrenia suffer from a few to a dozen relapses in their lifetime. The use of long-acting injectable (LAI) antipsychotics in the treatment of schizophrenia is associated with less frequent recurrences of psychotic symptoms, better compliance, and better quality of life. The aim of the report is to present the findings of the successful management of treatment-resistant schizophrenia in a patient with persistent non-compliance using a combination of typical and atypical LAI antipsychotics. Since there was a history of non-adherence (irregular controls in outpatient clinics) by the patient, clozapine was not considered a therapeutic option. At the start of the treatment, olanzapine LAI was administered to the patient at a dosage of 300 mg fortnightly because of the good response and tolerance reported in the previous treatment. The treatment was continued for several weeks, and because of the persistence of constant delusions, labile affect, and aggressive behavioral tendencies, a second antipsychotic, zuclopenthyxole, was added, which was initially administered orally. After 4 weeks of combined treatment, the patient's mental state improved. There was no report of delusions, and his mood was much more stable. Zuclopenthyxole was switched to the LAI antipsychotic form due to the patient's history of persistent non-compliance, lack of insight into the disease, and the risk of aggressiveness toward others. Then, 200 mg of zuclopenthyxole decanoate was administered fortnightly. The patient was discharged from the hospital without any symptoms of delusions or hallucinations. The patient's clinical state presented negative symptoms, of which avolition and diminished social activity were dominant. The patient tolerated the treatment well, and sedation and extrapyramidal symptoms were not observed. The patient continued the injections alternately (one injection per week) to obtain regular visits to the outpatient clinic.